Mass Media Analysis: Contribution of Millennials in the Success of the 2019 Election in Indonesia - Asniati Fajri, Uli; Sarofah, Riska; Fadli, Yusuf; Ginanjar Suryatman, Arif; Chumaedy, Ahmad (Universitas Muhammadiyah Yogyakarta, 2020)
Successful elections have an important objective in the quality of holding an election. millennials have political power that makes a significant contribution to the candidates. The many millennials will determine how much they will contribute to the 2019 elections in Indonesia. This is so as a reference in the objectives of benchmarks for the next election as well as for political parties and candidates. Thus, political participation will increase if millennials use their voting rights as a form of contribution to the success of the 2019 elections in Indonesian. Thus the researchers used a qualitative method with Nvivo 12 plus descriptive analysis techniques using the Crosstab Analysis, Cluster Analysis, Concept Map and Project Map Analysis, and Discourse Analysis features. There are three stages of the process, the first is Ncapture website and article, the second stage is analyzing with Nvivo 12 plus to read text and content that has the same meaning, words, and context that make interrelations between the website and article; the third stage of the discourse analysis is the analysis and meaning of a relevant website and article content. The conclusion of this study is knowing the contribution of millennials to the success of the 2019 elections in Indonesia.